Transcription expression of gene encoding cathelicidin CATHL4 in Vietnam indigenous yellow cattle - Tuoi, Do Thi; Anh, Tran Thi Thuy; Lan, Pham Doan; Van, Nguyen Thi Hong (Academia Journal of Biology, 2021)
Cathelicidins, a family of host-defence peptides, are present in a diverse range of species, including fish, amphibians, birds, reptiles, and mammals. The evidence for the role of these cationic antimicrobial peptides in innate host defenses is convincing from the data of animal model and transgenic animal experiments as well as wildlife or domestic animals, indicating that the peptides protect against inflammatory and immune system after induction by bacterial infection. In this study, we present the assessment of transcription expression of CATHL4 gene which encodes indolicidin, a cathelicidin from indigenous yellow cattle of Vietnam. The research focused on RNA samples extracted from lung tissues and lymph node collected from diseased cattle which died of infectious respiratory symptoms and the healthy cattle which were slaughtered for food purposes. By quantitative real-time PCR, the relative expression of transcripts was determined and analyzed using the expression of YWHAZ gene as reference. The results showed that this gene was abundantly expressed at a higher level in tissues of the diseased cattle than in those of the healthy ones. In both infection and healthy states, the expression of CATHL4 in lymph nodes were higher than in lung tissues. This indicated that CATHL4 (indolicidin) may participate in functions against infectious pathogens.